1992
DOI: 10.2307/2409875
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Genetic Structure in Two Tamarack [Larix laricina (Du ROI) K. Koch] Populations with Differing Establishment Histories

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 11 publications
1
41
1
1
Order By: Relevance
“…The discrepancies among studies may be because of factors such as percentage of tree removal (final forest density), level of gene inflow from the surrounding forest and level of genetic relatedness between the trees left after harvesting. Spatial analyses have shown some level of clustering of genotypes within populations of other conifers (Knowles et al, 1992;Cavers et al, 2005). However, cluster sizes are quite small (5-50 m across), suggesting that they are primarily a result of limited seed dispersal, and that the clusters are made up of close relatives; Knowles et al (1992) compared spatial genetic clustering in two stands of Larix laricina.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The discrepancies among studies may be because of factors such as percentage of tree removal (final forest density), level of gene inflow from the surrounding forest and level of genetic relatedness between the trees left after harvesting. Spatial analyses have shown some level of clustering of genotypes within populations of other conifers (Knowles et al, 1992;Cavers et al, 2005). However, cluster sizes are quite small (5-50 m across), suggesting that they are primarily a result of limited seed dispersal, and that the clusters are made up of close relatives; Knowles et al (1992) compared spatial genetic clustering in two stands of Larix laricina.…”
Section: Discussionmentioning
confidence: 98%
“…Spatial analyses have shown some level of clustering of genotypes within populations of other conifers (Knowles et al, 1992;Cavers et al, 2005). However, cluster sizes are quite small (5-50 m across), suggesting that they are primarily a result of limited seed dispersal, and that the clusters are made up of close relatives; Knowles et al (1992) compared spatial genetic clustering in two stands of Larix laricina. The stand had naturally regenerated after clear-cutting, presumably by a few remnant individuals scattered within the stand, and showed significant spatial clustering of genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, Boyle et a!. (1990), Xie & Knowles (1991), Knowles et al (1992) and Geburek (1993) found differences in spatial structure between stands of the same species, some of which could be interpreted as the result of different colonization histories.…”
Section: Introductionmentioning
confidence: 93%
“…Strong structuring has also been detected using spatial autocorrelation in a population in which vegetative reproduction and limited dispersal of pollen and seeds were observed (Shapcott, 1995). It has also revealed striking differences in genetic structure between populations with differing histories of anthropogenic disturbance (Knowles et al, 1992;Takahashi et al, 2000).…”
Section: Introductionmentioning
confidence: 81%